Heterogeneity of enterochromaffin cells within the gastrointestinal tract. Issue 6 (June 2017) - Diwakarla, S.; Fothergill, L. J.; Fakhry, J.; Callaghan, B.; Furness, J. B.
Abstract: Enterochromaffin cells were the first endocrine cells of the gastrointestinal tract to be chemically distinguished, almost 150 years ago. It is now known that the chromaffin reaction of these cells was due to their content of the reactive aromatic amine, 5‐hydroxytryptamine (5‐HT, also known as serotonin). They have commonly been thought to be a special class of gut endocrine cells (enteroendocrine cells) that are distinct from the enteroendocrine cells that contain peptide hormones. The study by Martin et al. in the current issue of this journal reveals that the patterns of expression of nutrient receptors and transporters differ considerably between chromaffin cells of the mouse duodenum and colon. However, even within regions, chromaffin cells differ; in the duodenum there are chromaffin cells that contain both secretin and 5‐HT, cholecystokinin and 5‐HT, and all three of secretin, cholecystokinin, and 5‐HT. Moreover, the ratios of these different cell types differ substantially between species. And, in terms of function, 5‐HT has many roles, including in appetite, motility, fluid secretion, release of digestive enzymes and bone metabolism. The paper thus emphasizes the need to define the many different classes of enterochromaffin cells and relate this to their roles. Abstract : Enterochromaffin cells have commonly been thought to be a special class of gut endocrine cells that are distinct from the enteroendocrine cells that contain peptide hormones. This review indicates that they overlap with peptide hormone‐containing cells and exhibit considerable heterogeneity.